Milices Maï-Maï, Dénonciation De L’impérialisme Et Politisation Des Masses Rurales Au Maniema (RDC) - Misako, Fraternel Amuri (European Scientific Journal, ESJ, 2017)
Based on a documentary inquiry aimed at reconstructing the processes of denunciation of imperialism associated with the Congolese Rally for Democracy (RCD)’s war in the Democratic Republic of Congo (DRC), by the maï-maï militia of Maniema, the article examines under the lens of historical criticism (heuristic and hermeneutic) the politicoideological contents of the essential documents whose impact on the rural masses remains crucial: their over-politicization of the latter. The study shows how a political mobilization that initially targeted awareness-raising for the recruitment of new combatants among rural Congolese youths has reactivated the protesting reflex of the rural populations both towards the rebels and their Rwandan allies, and maï-maï combatants. The repeated abuses of the maï-maï militias have thus brought down the nationalist mask which their ideological propaganda maintained until then. The pervasive activism of youths and especially the emergence of radicalized groups confirm the thesis of political violence as an indicator of democratic deficiencies of a weakened state through processes of globalization badly assumed in the African Great Lakes area.